Lacrimal bone cyst–a case report - Che Mohamed, Siti Kamariah; Yunus, Rohaizan; Ahmed Khan, Shamim (2007)
Introduction: Bone cyst is a rare benign bone tumour which normally affects the vertebral region or long bones. Despite its benign in nature, this lesion is expansile and may cause local compression and destruction of bone and soft tissues. Involvement of facial bones is very uncommon, and the lacrimal bone is very rare. Diagnosis usually achieved by radiological investigations, operative findings, and confirmed by histopathological findings. In achieving the diagnosis, it is very important to correlate the clinical, radiological and histological features of the entity to avoid confusion with other possibly neoplasms. Excision of the cyst provides complete cure for the patient. Case report: A 15 year-old Malay girl who presented with progressive right eye proptosis for 4 years duration. However, the vision was good and no opthalmoplegia or diplopia. She had recurrent history of sneezing, but no nasal blockage, epistaxis or nasal pain. The nasal symptom was controlled by nasal spray. She had 1 episode of eye infection in October 2005 and was treated as out-patient. CT scan paranasal sinus done in June 2006 suggests the presence of a large right lacrimal bone cyst. Removal of bone cyst, right uncinectomy, maxillary antrostomy, bulla ethmoidectomy and removal of small part of right frontal process of maxilla was done in December 2006. Following operation, she was well and free from symptoms.